Korelasi Model Pembelajaran Kooperatif Tipe TGT dan Motivasi Belajar Pendidikan Agama Kristen - Enri Yana Putri Enos; Tri Supartini; Sarce Rien Hana; Hengki Wijaya (Didache: Journal of Christian Education, 2021)
The problem in this study is the lack of student motivation in following Christian Religious Education subjects. For this reason, the purpose of this study was to determine the extent of the effect of the cooperative learning model of the team games tournamnet type on the motivation to learn Christian Religious Education in seventh grade students of SMP Negeri 1 Simbuang Tana Toraja. The author uses the method of distributing questionnaires to 20 students in the form of open statements and open interviews to 10 students. The purpose of conducting interviews is to strengthen the results of the questionnaires distributed and direct observations. From the correlation results of data analysis using SPSS, it shows that the team games tournament type cooperative learning model has an effect on students' intrinsic motivation with a significant result, namely 0.671 which is in a strong/high relationship, while the Teams Games Tournament on extrinsic motivation gets a significant result, namely 0.479 which is at moderate/moderate relationship. Students' learning motivation increases both intrinsic motivation and extrinsic motivation. Thus, it can be concluded that the team games tournament type cooperative learning model has an effect on students' learning motivation.Â